2008
DOI: 10.1097/ccm.0b013e31816f49ac
|View full text |Cite
|
Sign up to set email alerts
|

Changes in B-type natriuretic peptide improve weaning outcome predicted by spontaneous breathing trial

Abstract: Measuring the percentage change in the BNP level during a SBT may help improve the predictive value of SBT on weaning outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 34 publications
(28 reference statements)
2
63
1
3
Order By: Relevance
“…Similar to other researchers, we found that baseline hemodynamic values do not help in predicting weaning outcomes. Chien at al 23 found no difference in baseline BNP levels for patients in whom weaning was unsuccessful, but patients in whom extubation was unsuccessful had significantly higher levels of BNP at the end of the trial. The possibility of managing fluid levels on the basis of BNP levels during weaning was tested by Mekontso-Dessap et al 24 in a randomized control trial.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other researchers, we found that baseline hemodynamic values do not help in predicting weaning outcomes. Chien at al 23 found no difference in baseline BNP levels for patients in whom weaning was unsuccessful, but patients in whom extubation was unsuccessful had significantly higher levels of BNP at the end of the trial. The possibility of managing fluid levels on the basis of BNP levels during weaning was tested by Mekontso-Dessap et al 24 in a randomized control trial.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating this threshold value of BNP into the routine SBT in a subsequent validation study increased the extubation success rate from 78% to 95%. 45 Even though the above studies did not focus entirely on the HRFF population, these tools could be valuable in this population, which is more likely to have left (systolic and diastolic dysfunction) and right heart dysfunction.…”
Section: Other Methods To Assess Hrff Patientsmentioning
confidence: 99%
“…45 The weaning parameters commonly used in clinical practice assess only the respiratory load during an SBT and do not assess the imposed load on the heart. Studies have shown that measurements of central venous oxygen and serum brain natriuretic peptide (BNP) during an SBT could be useful tools to predict extubation failure due to cardiovascular dysfunction.…”
Section: Other Methods To Assess Hrff Patientsmentioning
confidence: 99%
“…11,12 Either BNP or NT-proBNP values may be used to detect cardiac dysfunction during weaning from mechanical ventilation, and may differentiate weaning success from failure. [13][14][15][16] There is a single published study focusing on difficult-to-wean patients with chronic obstructive pulmonary disease, 14 but little is known about the association between plasma NT-proBNP concentration and weaning outcomes in postoperative patients.…”
Section: Introductionmentioning
confidence: 99%